English Needs Analysis for Economics Students: An Exploratory Research - Saefullah, Hilmansyah; Nugraha, Sidik Indra (ELT in Focus, 2020)
Learning specific English relevant to the work field has currently been necessary for students studying in a specific subject field. Designing an English course for EFL students learning in a specific subject field requires a needs analysis. This research aims to investigate target needs of EFL students learning in economics field in order to be able to communicate both personally or professionally. The purpose of this research is also for developing an English syllabus for economics students based on the needs analysis. Through exploratory research design, this research involved 67 students from Economy Major in the third semester. The data about students’ target needs of English were collected through questionnaires adapted from Dudley-Evans & St. John (1998), Hutchinson & Waters (1987), and Nation & Macalister (2010). Based on the needs analysis, the results revealed that the English teaching should integrate four English skills (speaking, listening, writing, and reading) to accomodate the students’ needs.